(untitled) (Research, Society and Development, 2022)
Pre-hospital emergency care is a healthcare delivery service to victims of illnesses or accidents with a wide variety of health profiles. Ambulances may be a source of pathogenic microorganisms if not sanitized properly. Considering this, the present study aimed to evaluate the bacterial community present in different equipment and surfaces from ambulances used on pre-hospital care and verify the antibiotic resistance profile of the isolates. For that, three ambulances were chosen in unannounced visits, and eight sampling points were selected: wall inside the vehicle, cervical collar, spinal boards, bedsheets, masks, earplugs, head blocks and steering wheels. Pathogenic bacteria were isolated, identified and submitted to antimicrobial assays. A total of 144 samples were collected, and 33 different bacteria species were isolated. Among them, pathogenic genera Staphylococcus, Acinetobacter, Listeria and Ewingella. Staphylococcus, Acinetobacter, Listeria presented strains resistant to oxacilin, isolated from earplugs, spinal boards and masks which are in frequent contact with patients and rescuers. The results highlight the presence of pathogenic bacteria on surfaces and equipment that had been cleaned and deemed free of contagion.